2013
DOI: 10.1136/amiajnl-2012-001358
|View full text |Cite
|
Sign up to set email alerts
|

The discriminatory cost of ICD-10-CM transition between clinical specialties: metrics, case study, and mitigating tools

Abstract: ObjectiveApplying the science of networks to quantify the discriminatory impact of the ICD-9-CM to ICD-10-CM transition between clinical specialties.Materials and MethodsDatasets were the Center for Medicaid and Medicare Services ICD-9-CM to ICD-10-CM mapping files, general equivalence mappings, and statewide Medicaid emergency department billing. Diagnoses were represented as nodes and their mappings as directional relationships. The complex network was synthesized as an aggregate of simpler motifs and tabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 18 publications
0
75
0
Order By: Relevance
“…After the pediatric ICD-9-CM codes were mapped to ICD-10-CM codes and labeled into the above 5 categories, 14 an initial patient visit count and cost analysis were performed for each category. To appreciate potential clinical complexity inherent in the transition to ICD-10-CM, the convoluted codes were evaluated by physicians and classified into to 1 of 4 categories: information loss, overlapping categories, inconsistent, or consistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the pediatric ICD-9-CM codes were mapped to ICD-10-CM codes and labeled into the above 5 categories, 14 an initial patient visit count and cost analysis were performed for each category. To appreciate potential clinical complexity inherent in the transition to ICD-10-CM, the convoluted codes were evaluated by physicians and classified into to 1 of 4 categories: information loss, overlapping categories, inconsistent, or consistent.…”
Section: Discussionmentioning
confidence: 99%
“…A similar analysis revealed that 18% of adult oncology codes, 31% of emergency department codes, and 55% of hospital procedure codes are convoluted, showing variability in potential coding challenges by type of practice and the importance of understanding potential issues associated with codes commonly used by each specialty (A.D.B., unpublished data). 14,16 To assist with analysis of data that span the transition time frame (2015-2016), the American Medical Association suggests mapping in the direction with the most data (initially map ICD-10-CM back to ICD-9-CM; then, as more ICD-10-CM codes are used, map ICD-9-CM to ICD-10-CM). 17 However, using the GEMs files for simple transitions will miss a large number of codes: for example, if mapping from ICD-9-CM to ICD-10-CM using GEMs you map to only 24% of ICD-10-CM codes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,14 The mappings were examined by pediatricians for clinical accuracy, and financial analysis of the findings was conducted. The study was approved by the University of Illinois Institutional Review Board.…”
Section: Overviewmentioning
confidence: 99%
“…Boyd et al 14 provided classification for mapping on the basis of on how codes associate with each other. The ICD-9-CM codes were categorized into 5 categories on the basis of how they map to ICD-10-CM: identity (where the codes are equivalent), class-to-subclass (1 ICD-9-CM code going to multiple ICD-10-CM codes), subclass-to-class (multiple ICD-9-CM codes to 1 ICD-10-CM code), no transition (no mapping to ICD-10-CM), and convoluted (a complex mapping of ICD-9-CM to and from ICD-10-CM; see Fig 1).…”
Section: Categorization Of Complexity Of Mappingmentioning
confidence: 99%